2021
DOI: 10.1002/jsfa.11394
|View full text |Cite
|
Sign up to set email alerts
|

Deficit drip irrigation based on crop evapotranspiration and precipitation forecast improves water‐ use efficiency and grain yield of summer maize

Abstract: BACKGROUND Limited and erratic precipitation with inefficient irrigation scheduling often leads to an unstable crop yield and low water‐use efficiency (WUE) in semi‐arid and semi‐humid regions. A 2‐year field experiment was conducted to evaluate the effect of three irrigation strategies (conventional irrigation (CK), full‐drip irrigation (FI), based on crop evapotranspiration and precipitation forecast, and deficit drip irrigation (DI) (75% FI)) on photosynthetic characteristics, leaf‐to‐air temperature differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…Zhou et al [92] found higher grain yields of hybrid rice due to improved WUE and crop-water relationships under water-deficit conditions. In addition to deficit irrigation, micro-irrigation, deficit drip irrigation, and planting patterns can also enhance WUE under drought-prone conditions [93][94][95]. However, productivity and WUE of hybrid crop cultivars can also strongly depend on agronomic practices and climatic conditions, e.g., Buczek [96] reported that grain yield and quality of hybrid wheat varied significantly with tillage practices, whereas Rezaei et al [97] found that phenology of wheat cultivars varied climatic changes.…”
Section: Discussionmentioning
confidence: 99%
“…Zhou et al [92] found higher grain yields of hybrid rice due to improved WUE and crop-water relationships under water-deficit conditions. In addition to deficit irrigation, micro-irrigation, deficit drip irrigation, and planting patterns can also enhance WUE under drought-prone conditions [93][94][95]. However, productivity and WUE of hybrid crop cultivars can also strongly depend on agronomic practices and climatic conditions, e.g., Buczek [96] reported that grain yield and quality of hybrid wheat varied significantly with tillage practices, whereas Rezaei et al [97] found that phenology of wheat cultivars varied climatic changes.…”
Section: Discussionmentioning
confidence: 99%
“…Beishan and Qinling Mountains divide Shaanxi Province into three natural regions: the northern Shaanxi Plateau, the central Guanzhong Plain, and the southern Qinba Mountains (Nascimento 2020, Yue et al 2021). The Guanzhong Plain has been known as a granary since ancient times (He and Zhou 2016, Forte et al 2017, Ruis 2021, Simão and Johnston 2021, Lu et al 2022). In the process of maize planting, it is necessary to study the main agronomic traits and their correlation with yield, to clarify the main factors affecting yield, and to provide a basis for selecting superior hybrids (Fernando 2020, Hou et al 2020, Tao 2020.…”
Section: Introductionmentioning
confidence: 99%
“…Maximum nitrogen use efficiency was obtained with good quality irrigation treatment [ 13 ]. Deficit drip irrigation based on crop evapotranspiration and precipitation forecast is beneficial to improve crop water use efficiency and maintain high grain yield in semi-arid and semi-humid regions [ 14 ]. While the effects of irrigation treatments on average dry matter contents of the lines were not found to be significant, significant differences were observed in water use efficiency and kernel yield of dent corn lines [ 15 ].…”
Section: Introductionmentioning
confidence: 99%